Pengaruh Analisis Fundamental dan Risiko Sistematik terhadap Harga Saham pada Pasar Modal Syariah - Robiatul Adawiyah Sinambela; Novien Rialdy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Islamic capital market has attractive investment potential for investors. Therefore, investors need to understand stock price information, including fundamental analysis (ROE, DER, EPS) and systematic risk that occurs from outside the company (beta), before deciding to buy or sell shares of a stock. The differences between theory and current phenomena are blurring further research. The formulation of the problem is to find out whether there is any influence of fundamental analysis (ROE, DER, and EPS as well as BETA systematic risk) which can influence the share price of a company. This type of research uses quantitative methods. The data used is secondary data such as company securities reports. This population includes all companies listed on the Jakarta Islamic index (JII) in 2020 - 2022. From these findings, we can conclude that in some cases only ROE and EPS affect share prices. Meanwhile, DER and systematic risk (BETA) have no effect on share prices